P.13.JHA - Jade Hawkins (2013)
Inspired by memories of travels & trips to museums, for this project designer tried to capture the curosity & excitement of encountering new cultures & objects. It is an eclectic & curated mix of world cultures, celebrating the colours of patterns & textures created by people all over the world.